Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


Consider, a^(1/2)b^(1/2)=(ab)^(1/2) and (a²b²)^{2/3}=(ab)^(4/3) There product is (ab)^{1/2 + 4/3}=(ab)^{11/6}. (ab)^{(11/6)*(-1/2)}=(ab)^{-11/12} Hence, (a^(1/3)*(ab)^{-11/12})^4=a^(-7/3)*b^(-11/3)
1 5 1
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts